High hydrostatic pressure-modified “Reka” blueberry pectin and its complexes with different anthocyanins: Multiscale structural changes, rheological properties, and antioxidant characteristics - Chang Tan; Chenyang Shi; Xiaoqian Hu; Hanchi Ma; Youlin Xue; Tiejing Li; Chongting Guo; Shan Wang; Weixuan Li; Chong Ning (Food Hydrocolloids, 2026)

Molecular characterization and biological characteristics of a highly pathogenic recombinant ALV-J strain (HUE2023) with cross-clade gp85 recombination - Chao Li; Ziqing Tan; Liwen Tong; Yanmei Jiang; Ruihan Zhang; Yifeng Shan; Mengting Li; Zhiyi Yang; Jinpeng Xu; Yuxiang Shi; Yongxiang Liu (Veterinary Microbiology, 2026)

Eco-hydrological processes in controlling vertical and lateral carbon fluxes in a subtropical salt marsh: Insights from modeling and scale-resolved analysis - Ke-Hua Zhu; Li-Shan Tan; Guan-Xun Wang; Li-Ming Xue; Zeng-Feng Li; Hua-Yu Chen; Qing Lyu; Bo-Fei Li; Wei Zhao; Christian Schwarz; Zhen-Ming Ge (CATENA, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Mechanism-anchored ecological risk assessment of phthalates in coastal waters: Bridging environmental fate and molecular toxicity via an AOP framework - Shao-Yang Bu; Li-Ju Tan; Yan-Shan Chen; Kun Lin; Jiang-Tao Wang (Marine Pollution Bulletin, 2026)

Peak prediction and emission reduction pathways of building operational carbon emissions in Eastern China - Shanbi Peng; Wen Li; Enbin Liu; Xianbin Zheng; Xinyu Shan; Jiayi Tan (Journal of Cleaner Production, 2026)

Deep eutectic solvent-based green extraction and antioxidant evaluation of polyphenols from Malus coronaria crabapple fruits - Shan Wang; Quanyi Sun; Yaqian Bai; Jiayi Wang; Wanqi Bi; Dezheng Zhang; Wenbin Han; Chong Ning; Chongting Guo; Weixuan Li; Fengqing Hu; Chang Tan (Food Chemistry, 2026)

Stability problems of Pt coating on porous transport layers in PEM water electrolyzers under startup-shutdown cycling - Xiaoyun Shi; Jiwei Shan; Runcheng Zhang; Xiaoke Li; Yipeng Zhang; Chang Liu; Aidong Tan; Ying Wang; Xiaoyi Zhu; Xueqiang Gao; Jianguo Liu (Chemical Engineering Journal, 2026)

Intracranial EEG reveals working memory-related dynamics and connectivity in human white matter - Shen Zhang; Peng-Hu Wei; Longzhou Xu; Chao Zhang; Na Ao; Haoshu Xu; Yanfeng Yang; Lirou Tan; Zhilin Li; Yali Huang; Jin Li; Jing Liu; et al. (Science Bulletin, 2026)

Integrated lipidomics and transcriptomics reveal different lipid profiles and metabolic pathways in cultured fats from porcine subcutaneous adipocytes and fibro-adipogenic progenitors - Xin Gu; Qianqian Li; Shiqi Liu; Lay Poh Tan; Teresa G. Valencak; Tizhong Shan (Food Chemistry, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Sex-specific responses of intestinal health, microbiota composition, and transcriptome profiles in golden pompano (Trachinotus blochii) subjected to hypoxia and reoxygenation - Xiao Kun Wang; Shan Ying Han; Ze Xin Zhong; Zeng Tan Hu; Tian Xiu Li; Yue Gu; Chun Xiu Jin; Tian Jiang; Fei Biao Song; Jian Luo; Jun Long Sun (Frontiers in Marine Science, 2026)
Introduction Driven by global climate change and coastal eutrophication, severe hypoxic events have become a primary environmental stressor in marine ecosystems, posing a critical threat to commercially vital teleosts like the golden pompano ( Trachinotus blochii ). Understanding the dimorphic physiological and microbial responses between sexes under such stress is crucial for developing targeted mitigation strategies. Methods Golden pompano were subjected to hypoxia stress (3.0 ± 0.2 mg/L) for 14 days, followed by restoration of dissolved oxygen to normoxic state (7.0 ± 0.2 mg/L) and cultivation for another 14 days. Subsequently, the histology ( n = 3), digestive enzyme activity ( n = 9), microbial composition ( n = 3), and transcriptome ( n = 3) of intestinal tissue were evaluated. Results Hypoxia induces marked physiological stress and a shift toward intestinal dysbiosis across both genders, manifested by damaged intestinal integrity, oxidative stress, and an increased abundance of opportunistic pathogens (e.g., Spirochaetes ). Although reoxygenation further deteriorates the histological condition of female intestinal tissue, it also triggers more significant molecular and enzyme activity rebound effects compared to males. Moreover, females exhibit significant upregulation of lipid metabolism, antioxidant defense mechanisms, and key signaling pathways, suggesting that they may have adopted a high-energy “compensatory recovery” strategy. Correlation analyses reveal that these microbial shifts are closely linked to host metabolic regulation: beneficial bacteria ( Pseudoalteromonas and Lactococcus ) support sterol transport and signaling homeostasis, while opportunistic taxa ( Brevinema ) negatively impact lipid synthesis. Discussion Our findings reveal a distinct gender dimorphism in the hypoxia and reoxygenation response, providing a theoretical foundation for sex-specific management and nutritional interventions in golden pompano aquaculture.

Dual-functional NiCo2O4 nanofibers/chitosan aerogel for efficient solar evaporation and bacterial removal - Yuangao Li; Shan Chen; Rengfeng Luo; Liyan Xue; Heng Chen; Fengzhi Tan; Minzhong Huang; Zhaoli Liu; Fan Yang (Journal of Environmental Chemical Engineering, 2026)

Application and research progress of hydrocolloid-anthocyanin functional composite system: A review - Xiaoqian Hu; Chenyang Shi; Chongting Guo; Shan Wang; Chong Ning; Weixuan Li; Chang Tan (Food Research International, 2026)

Balancing rice production and greenhouse gas mitigation: assessing the feasible potential of agricultural practices - Qiang Xu; Dicai Ao; Xin Li; Xiangcheng Zhu; Zihao Wang; Yi Yang; Pete Smith; Baojing Gu; Lei Liu; Jinyang Wang; Shuhao Tan; Ziyin Shang; et al. (Resources, Conservation and Recycling, 2026)

Mitigating antibiotic resistance genes in chicken manure composting through hydrothermal carbonization solution of sewage sludge - Guangchun Shan; Ke Wang; Weiguang Li; Zhenling Li; Jie Liu; Lin Zhu; Xiaoshu Wei; Beidou Xi; Wenbing Tan (Process Safety and Environmental Protection, 2026)

One new rearranged pyranone derivative with antibacterial activity from Xylaria curta YSJ-5 - Shan-Shan Wei; Dao-Jun Rong; Jia-Ying Lai; Chen Chen; Si-Ran Li; Zhong-Hua Yu; Hai-Bo Tan (Phytochemistry Letters, 2025)

Anthraquinone sites engineering of covalent organic frameworks enables efficient and selective 1O2 generation via directed oxidation of peroxymonosulfate - Yuzheng Wu; Jinyi Tan; Zifan Li; Luwen Liang; Bing Chen; Xinwen Ou; Shan Yao; Guiquan Che; Youqun Wang; Bin Han (Journal of Hazardous Materials, 2025)

Development of a sonodynamic approach for Listeria monocytogenes inactivation and quality preservation in strawberries - Zifei Liu; Lingdai Liu; Wendi Chen; Wei Shan Tan; Dan Li (Food Research International, 2025)

Three new acidic polysaccharides from steamed Polygonatum cyrtonema Hua modulate immunomodulatory activities via TLR4-mediated MAPK and NF-κB pathways - Yanling Wang; Lanlan Wu; Yuan Zhang; Qianglai Tan; Shan Huang; Yuhuan Li; Huanxin Wang; Chaoxiang Chen; Weijing Wu (Food Bioscience, 2025)

Multiple competitive superiority made a great successful invasion of Spartina alterniflora in Eastern China: hints for management - Shi-Hua Li; Zhen-Ming Ge; Li-Shan Tan; Li-Na Xie; Ya-Lei Li (Journal of Environmental Management, 2025)

Extraction, purification, structural characterization, biological activity, structure-activity relationship, and applications of polysaccharides derived from Polygonatum sibiricum: A review - Jiasu Wu; Chang Tan; Hongye Li; Siya Wang; Xingkui Wang; Shan Wang; Chong Ning; Weixuan Li; Chongting Guo (Trends in Food Science & Technology, 2025)

Methane adsorption capacity of shale in the upper Permian Longtan Formation in the eastern Sichuan–northern Guizhou region, South China - X-M. Li; X. Tang; S-B. Guo; Y-S. Shan; E-D. Deng; C-L. Lan; B-D. Tan (Australian Journal of Earth Sciences, 2025)

CRISPR/Cas-powered “sweet” DNA nano-sponge for highly sensitive detection of pathogen nucleic acid with portable personal glucometer - Huiling You; Jingwen Shan; Yang Bai; Ruochen Yang; Shulin Tan; Yueqing Gu; Baicun Li; Haiping Wu; Yunlong Liu (Chemical Engineering Journal, 2025)

Efficient regeneration of Cu-SSZ-13 NH3-SCR catalysts deactivated by Na, P and (Na+P) poisoning - Shoute Zhang; Jingyi Tan; Ying Meng; Xiaomin Tang; Yulong Shan; Jinpeng Du; Dongsheng Xia; Weiquan Cai; Tao Li (Chemical Engineering Journal, 2025)

Spatial and temporal characteristics of volatiles in the Cenozoic mantle beneath eastern China - Qianling Zhou; Chenglong Yu; Yang-Yang Wang; Dongbo Tan; Erhao Shan; Dongyong Li; Xiaoxia Wang; Yigan Lu; Fengtai Tong; Yilin Xiao (Lithos, 2024)

Changes in the metabolic score for insulin resistance index for risk prediction of stroke in middle-aged and older Chinese population - Tingting Wang; Zhiheng Yi; Yuhan Tan; Yangshen Huang; Tengli Li; Shan Gao; Yaoling Wu; Weiduan Zhuang; Shaowei Guo (EPMA Journal, 2024)

The role of urban green space landscape patterns in the synergistic prevention of PM2.5 and ozone pollution: A case study in Shenyang city, China - Yu Li; Leichang Huang; Siwen Li; Min Cao; Peng Tan; Qiaochu Wang; Huan Meng; Shan Yin; Weikang Zhang (Atmospheric Pollution Research, 2024)

Quinosumycin, a novel anti-MRSA thioether-linked quinolinone-quinazolinone heterodimer from a marine actinomycete Streptomyces diastaticus NBU2966 - Shuangling Tan; Yang Liu; Haonan Fu; Yutong Xue; Fangjian Feng; Jinling Li; Xiaojun Yan; Sitong Wu; Shan He; Lijian Ding (Journal of Oceanology and Limnology, 2024)

Mechanistic Insights and Potential Therapeutic Implications of NRF2 in Diabetic Encephalopathy - Xin Cheng; Yejun Tan; Hongli Li; Zhen Zhang; Shan Hui; Zheyu Zhang; Weijun Peng (Molecular Neurobiology, 2024)

Cytotoxic xanthanolide sesquiterpenes from the fruits of Xanthium italicum Moretti - Yu-Tong Li; Cheng-Yong Tan; Jiang Fu; Hai-Qiang Wang; Yun-Bao Liu; Shuang-Gang Ma; Yong Li; Jing Qu; Shi-Shan Yu (Phytochemistry, 2024)

Co-hydrothermal carbonization of municipal sludge and agricultural waste to reduce plant growth inhibition by aqueous phase products: Molecular level analysis of organic matter - Guangchun Shan; Weiguang Li; Jie Liu; Shanshan Bao; Zhenling Li; Shuncai Wang; Lin Zhu; Beidou Xi; Wenbing Tan (Science of The Total Environment, 2024)

Effect of aqueous phase from hydrothermal carbonization of sewage sludge on heavy metals and heavy metal resistance genes during chicken manure composting - Guangchun Shan; Xiaoshu Wei; Weiguang Li; Jie Liu; Shanshan Bao; Shuncai Wang; Lin Zhu; Beidou Xi; Wenbing Tan (Journal of Hazardous Materials, 2024)

Semi-quantifying vertical sedimentary succession and microfacies characterization from a delta system in a lacustrine basin, Huangqihai Lake, North China - Wenjun Kang; Shunli Li; Xin Shan; Chengpeng Tan (Sedimentary Geology, 2024)

Influence of goethite nanophase on rare-earth element patterns and enrichment in marine phosphates during early diagenesis - Jieqi Xing; Shan Li; Hongyan Wei; Jiaxin Xi; Xiaoju Lin; Yiping Yang; Haiyang Xian; Wei Tan; Jingming Wei; Jianxi Zhu (Chemical Geology, 2024)

Correlation of Immune-Inflammatory Response System (IRS)/Compensatory Immune-Regulatory Reflex System (CIRS) with White Matter Integrity in First-Episode Patients with Schizophrenia - Mengzhuang Gou; Wei Li; Jinghui Tong; Yanfang Zhou; Ting Xie; Ting Yu; Wei Feng; Yanli Li; Song Chen; Baopeng Tian; Shuping Tan; Zhiren Wang; et al. (Molecular Neurobiology, 2024)

Flexural performance of a prefabricated steel–UHPC composite deck under transverse hogging moment - Xingyu Tan; Zhi Fang; Xiaonan Wu; Xiukun Li; Yuan Liao; Shan Pei (Engineering Structures, 2024)

Design of an active-source seismic detection system based on illumination analysis and migration imaging experiments: considering the Zhuxi mining area as an example - Wen Li; Yong Chen; Shan-Hui Xu; Jiu-Peng Hu; Bao-Jin Liu; Yong-Peng Ouyang; Yin-Juan He; Ya-Li Tan; Xin-Sheng Hua; Jing-Jing Qin; Qian Li; Jia Jia (Applied Geophysics, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Tropical cyclone activity around Taiwan modulated by El Niño during 1900–1945 and 1970–2015 - Pei‐Hua Tan; Jau‐Ming Chen; Wei‐Teh Li; Hui‐Shan Chen (International Journal of Climatology, 2024)
Tropical cyclone (TC) activity around Taiwan is analysed via typhoon datasets compiled by the Central Weather Administration (CWA) for the pre‐satellite era of 1900–1945 (IE1) and the satellite era of 1970–2015 (IE2). Modulating processes imposed by El Niño years on active and inactive TC activity around Taiwan in the July–September season are examined and compared between IE1 and IE2. Analyses reveal coherent dynamic relationships between TC variability in Taiwan and large‐scale modulating processes; furthermore, modulating processes exhibit similar features between IE1 and IE2. El Niño years tend to have more (less) TC formation in the eastern (western) sector of the western North Pacific (WNP). In both IE1 and IE2, intensified TC activity around Taiwan is associated with northwestward TC tracks from the eastern WNP toward Taiwan assisted by a westward‐elongating cyclonic anomaly across the WNP and South China Sea. When a WNP cyclonic anomaly stretches northwestward toward oceans north of Taiwan, TCs from the tropical eastern WNP generally move northward toward oceans east of Taiwan to result in suppressed TC activity around Taiwan. The westward‐elongating anomalous cyclone is associated with an anomalous divergent centre over the Indian Ocean and an anomalous convergent centre in the tropical eastern Pacific over the 150°–130°W region. The northwestward‐extending anomalous cyclone connects with an anomalous divergent centre over the Maritime Continent and an anomalous convergent centre over the 130°–110°W region. Anomalous divergent and convergent centres displace westward (eastward) for active (inactive) TC types that are related to a more westward (eastward) maximum centre of anomalous warm waters in the tropical eastern Pacific. The above coherent dynamic relationships justify the reliability of TC records compiled by the CWA during IE1 and IE2.

Fatigue tests of multiplanar concrete-filled steel tubular KK-joints with inner ring stiffeners - Kang Wang; Xu-Hong Zhou; Seiichiro Tsutsumi; Jun-Xin Wu; Yu-Hang Wang; Ji-Ke Tan; Bin Wang; Shan Gao; Yu Li (Ocean Engineering, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Cortical thickness of the inferior parietal lobule as a potential predictor of relapse in men with alcohol dependence - Kebing Yang; Ruonan Du; Qingyan Yang; Rongjiang Zhao; Fengmei Fan; Song Chen; Xingguang Luo; Shuping Tan; Zhiren Wang; Ting Yu; Baopeng Tian; Thang M. Le; et al. (Brain Imaging and Behavior, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Macrogenomic analysis of the effects of aqueous-phase from hydrothermal carbonation of sewage sludge on nitrogen metabolism pathways and associated bacterial communities during composting - Guangchun Shan; Weiguang Li; Jie Liu; Wenbing Tan; Shanshan Bao; Shuncai Wang; Lin Zhu; Xinhao Hu; Beidou Xi (Bioresource Technology, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Biodegradability enhancement of waste lubricating oil regeneration wastewater using electrocoagulation pretreatment - Li-li Shan; Zhao Tan; Yu Chen; Ruo-shan Wang; Meng Zhang; Chang-long Pang; Yu-Hong Cui; Zhi-min Liao; Hong-qiang Ma; Ze-bing Zhu (Environmental Science and Pollution Research, 2023)

Impacts of land-use change on carbon dynamics in China's coastal wetlands - Li-Shan Tan; Zhen-Ming Ge; Shi-Hua Li; Ke Zhou; Derrick Y.F. Lai; Stijn Temmerman; Zhi-Jun Dai (Science of The Total Environment, 2023)

Magnetic field enabled spin-state reconfiguration for highly sensitive paper-based photoelectrochemical bioanalysis - Xiaoran Tan; Jiaxin Liang; Haihan Yu; Yuanyuan Chen; Li Shan; Shenguang Ge; Lina Zhang; Li Li; Jinghua Yu (Chemical Engineering Journal, 2023)

Urban agglomeration waterlogging hazard exposure assessment based on an integrated Naive Bayes classifier and complex network analysis - Mo Wang; Xiaoping Fu; Dongqing Zhang; Siwei Lou; Jianjun Li; Furong Chen; Shan Li; Soon Keat Tan (Natural Hazards, 2023)

IRAK-M Ablation Promotes Status Epilepticus-Induced Neuroinflammation via Activating M1 Microglia and Impairing Excitatory Synaptic Function - Xiao-Shan Liang; Ting-Lin Qian; Yi-Fan Xiong; Xiao-Tao Liang; Yue-Wen Ding; Xiao-Yu Zhu; Yun-Lv Li; Jie-Li Zhou; Le-Yi Tan; Wei-Peng Li; Wei Xie (Molecular Neurobiology, 2023)

Liver-cell protective pyridones from the fungi Tolypocladium album dws120 - Xiao-Qian Wu; Jing Li; Xi Zhou; Jing Wang; Yu-Fen Tan; Ji-Song Mo; Shao Liu; Kang-Ping Xu; Gui-Shan Tan; Wei Zhang; Wen-Xuan Wang (Phytochemistry, 2023)

Preparation and evaluation of ovalbumin-fucoidan nanoparticles for nicotinamide mononucleotide encapsulation with enhanced stability and anti-aging activity - Shan Sun; Xuedi Zhang; Jiaxuan Li; Yu Li; Chengfu Zhou; Siyuan Xiang; Mingqian Tan (Food Chemistry, 2023)

Effect of the aqueous phase from the hydrothermal carbonization of sewage sludge as a moisture regulator on nitrogen retention and humification during chicken manure composting - Guangchun Shan; Weiguang Li; Wenbing Tan; Shanshan Bao; Jie Liu; Shuncai Wang; Lin Zhu; Li Chen; Beidou Xi (Chemical Engineering Journal, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Effect of hydrochar on antibiotic-resistance genes and relevant mechanisms during chicken manure composting - Guangchun Shan; Jie Liu; Bin Zhu; Wenbing Tan; Weiguang Li; Zhurui Tang; Xinhao Hu; Lin Zhu; Beidou Xi (Journal of Hazardous Materials, 2023)

Physical character, total polyphenols, anthocyanin profile and antioxidant activity of red cabbage as affected by five processing methods - Si Tan; Xin Lan; Shan Chen; Xin Zhong; Wenfeng Li (Food Research International, 2023)

Evaluating the aqueous phase obtained from hydrothermal carbonization of municipal sludge as possible liquid fertilizer for plant growth: An analysis of heavy metals and their molecular composition - Guangchun Shan; Weiguang Li; Shanshan Bao; Jie Liu; Lin Zhu; Wenbing Tan (Journal of Cleaner Production, 2023)

Early 7,8-Dihydroxyflavone Administration Ameliorates Synaptic and Behavioral Deficits in the Young FXS Animal Model by Acting on BDNF-TrkB Pathway - Yu-shan Chen; Si-ming Zhang; Wei Tan; Qiong Zhu; Chao-xiong Yue; Peng Xiang; Jin-quan Li; Zhen Wei; Yan Zeng (Molecular Neurobiology, 2023)

Effects of persulfate-assisted hydrothermal treatment of municipal sludge on aqueous phase characteristics and phytotoxicity - Guangchun Shan; Weiguang Li; Yujie Zhou; Shanshan Bao; Lin Zhu; Wenbing Tan (Journal of Environmental Sciences, 2023)

Association between co-exposure of polycyclic aromatic hydrocarbons and chronic obstructive pulmonary disease among the US adults: results from the 2013–2016 National Health and Nutrition Examination Survey - Lin Wen; Xiaosong Ben; Zhiyu Yang; Yingying Wu; Yuxuan Tan; Qian Chen; Huanzhu Liang; Yexin Li; Xiaomei Wu; Shan Liu; Xueqiong Weng; Dan Tian; et al. (Environmental Science and Pollution Research, 2023)

Planning of best management practices for watershed-scale pollution control: A simulation-based inexact fractional programming approach - Shuping Wang; Qian Tan; Chunhui Li; Shan Zhang; Tianyuan Zhang (Journal of Hydrology, 2023)

Effects and mechanism on cadmium adsorption removal by CaCl2-modified biochar from selenium-rich straw - Zongyu Gao; Dexin Shan; Jiahong He; Tao Huang; Yuan Mao; Haiping Tan; Huiting Shi; Tingzhen Li; Taiping Xie (Bioresource Technology, 2023)

Nitrogen loss, nitrogen functional genes, and humification as affected by hydrochar addition during chicken manure composting - Guangchun Shan; Weiguang Li; Jie Liu; Lin Zhu; Xinhao Hu; Wei Yang; Wenbing Tan; Beidou Xi (Bioresource Technology, 2023)

Energy and nutrient recovery by spent mushroom substrate-assisted hydrothermal carbonization of sewage sludge - Guangchun Shan; Weiguang Li; Shanshan Bao; Xinhao Hu; Jie Liu; Lin Zhu; Wenbing Tan (Waste Management, 2023)

Co-hydrothermal carbonization of agricultural waste and sewage sludge for product quality improvement: Fuel properties of hydrochar and fertilizer quality of aqueous phase - Guangchun Shan; Weiguang Li; Shanshan Bao; Yangyang Li; Wenbing Tan (Journal of Environmental Management, 2023)

Effects of waterlogging and elevated salinity on the allocation of photosynthetic carbon in estuarine tidal marsh: a mesocosm experiment - Ya-Lei Li; Zhen-Ming Ge; Li-Na Xie; Shi-Hua Li; Li-Shan Tan; Kasper Hancke (Plant and Soil, 2023)

Associations of single and multiple organophosphate pesticide exposure with female infertility in the USA: data from the 2015–2018 National Health and Nutrition Examination Survey - Yingying Wu; Xueqiong Weng; Shan Liu; Yuxuan Tan; Huanzhu Liang; Yexin Li; Lin Wen; Qian Chen; Chunxia Jing (Environmental Science and Pollution Research, 2022)

History of suicide attempts associated with the thinning right superior temporal gyrus among individuals with schizophrenia - Yi Yin; Jinghui Tong; Junchao Huang; Baopeng Tian; Song Chen; Shuping Tan; Zhiren Wang; Fude Yang; Yongsheng Tong; Fengmei Fan; Peter Kochunov; Neda Jahanshad; et al. (Brain Imaging and Behavior, 2022)

Quercetin Alleviates Demyelination Through Regulating Microglial Phenotype Transformation to Mitigate Neuropsychiatric Symptoms in Mice with Vascular Dementia - Zihu Tan; Guang Yang; Jing Qiu; Wenjing Yan; Yu Liu; Zhengling Ma; Jia Li; Jing Liu; Nan Shan (Molecular Neurobiology, 2022)

Trichocladabiflavone A, a chalcone-flavonone type biflavonoid from Selaginella trichoclada Alsto - Yang Xie; Xiao-Chang Yao; Lei-Hong Tan; Hong-Ping Long; Ping-Sheng Xu; Jing Li; Gui-Shan Tan (Natural Product Research, 2022)

A genetic-based population PK/PD modeling of methadone in Chinese opiate dependence patients - Dong Guo; Zhirong Tan; Xiaoya Lou; Shan Shi; Yan Shu; Honghao Zhou; Li Yu; Hong Yang (European Journal of Clinical Pharmacology, 2022)

Morphologic changes of simple star dunes during the growth process in Dunhuang, China - Zhi-shan An; Ke-cun Zhang; Li-hai Tan; Qing-he Niu; Ben-li Liu; Bai-cheng Niu (Journal of Mountain Science, 2022)

Economic Evaluation of Water-Saving Irrigation Practices for Sustainable Sugarcane Production in Guangxi Province, China - Shan-Shan He; Yuan Zeng; Zhao-Xu Liang; Yan Jing; ShiYun Tang; Baoqing Zhang; Haifeng Yan; Song Li; Tinglin Xie; Fang Tan; Ming Li (Sugar Tech, 2021)

Two new biflavanoids from Selaginella trichoclada Alsto - Yang Xie; Ping-Sheng Xu; Kang-Ping Xu; Zhen-Xing Zou; Gan Zhou; Dai Li; Dan Li; Xiao-Min Li; Jing Li; Gui-Shan Tan (Natural Product Research, 2021)

TRIM25 Rescues Against Doxorubicin-Induced Pyroptosis Through Promoting NLRP1 Ubiquitination - Xiaxia Wang; Zhexun Lian; Yiping Ge; Dongqiang Yu; Shan Li; Kai Tan (Cardiovascular Toxicology, 2021)

Comet Assay Evaluation of Lanthanum Nitrate DNA Damage in C57-ras Transgenic Mice - Gaochao Han; Zhuangsheng Tan; Haiming Jing; Junyu Ning; Zinan Li; Shan Gao; Guojun Li (Biological Trace Element Research, 2021)

Design, synthesis, and antidepressant/anticonvulsant activities of 3H-benzo[f]chromen chalcone derivatives - Qiu-Wan Tan; Li-Ya He; Zhi-Wen He; Wei-Hua Liu; Shan-Shan Zhang; Lin Lin; Hong-Li Yang; Li-Ping Guan (Medicinal Chemistry Research, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Correction to: Emodin alleviated pulmonary inflammation in rats with LPS-induced acute lung injury through inhibiting the mTOR/HIF-1α/VEGF signaling pathway - Xiaoqian Li; Cong Shan; Zhonghua Wu; Hongji Yu; Aidong Yang; Bo Tan (Inflammation Research, 2020)

Emodin alleviated pulmonary inflammation in rats with LPS-induced acute lung injury through inhibiting the mTOR/HIF-1α/VEGF signaling pathway - Xiaoqian Li; Cong Shan; Zhonghua Wu; Hongji Yu; Aidong Yang; Bo Tan (Inflammation Research, 2020)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

Evolution model of a modern delta fed by a seasonal river in Daihai Lake, North China: determined from ground-penetrating radar and trenches - Beibei Liu; Chengpeng Tan; Xinghe Yu; Xin Shan; Shunli Li (Frontiers of Earth Science, 2019)

Dune dynamics in the southern edge of Dunhuang Oasis and implications for the oasis protection - Zhi-shan An; Ke-cun Zhang; Li-hai Tan; Hu Zhang; Bai-cheng Niu (Journal of Mountain Science, 2018)

Mechanisms of Interaction Between an Arch Dam and Abutment Slope Using Physical Model Tests - Guanhua Sun; Shan Lin; Shengguo Cheng; Tan Sui; Chunguang Li; Hong Zheng (Rock Mechanics and Rock Engineering, 2018)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A new androstanoid metabolite from a soil fungus Curvularia borreriae strain HS-FG-237 - Li-Fei Liu; Hui Zhang; Huan Qi; Xiao-Ming Wang; Ji-Dong Wang; Gui-Shan Tan (Natural Product Research, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Frontotemporal Lobar Degeneration: Mechanisms and Therapeutic Strategies - Ya-Qing Li; Meng-Shan Tan; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

Ground-penetrating radar study of beach-ridge deposits in Huangqihai Lake, North China: the imprint of washover processes - Xin Shan; Xinghe Yu; Peter D. Clift; Chengpeng Tan; Shunli Li; Zhixing Wang; Dongxu Su (Frontiers of Earth Science, 2016)

Sedimentology and stratigraphic evolution of the fan delta at the Badaowan formation (lower Jurassic), Southern Junggar Basin, Northwest China - Chengpeng Tan; Xinghe Yu; Shunli Li; Xin Shan; Bintao Chen (Arabian Journal of Geosciences, 2016)

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Geochronology and geochemistry of Grenville-aged (1063 ± 16 Ma) metabasalts in the Shennongjia district, Yangtze block: implications for tectonic evolution of the South China Craton - Xiao-Fei Qiu; Hong-Mei Yang; Shan-Song Lu; Wen-Li Ling; Li-Guo Zhang; Juan-Juan Tan; Zhi-Xian Wang (International Geology Review, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

A two-tube multiplex real-time RT-PCR assay for the detection of four hemorrhagic fever viruses: severe fever with thrombocytopenia syndrome virus, Hantaan virus, Seoul virus, and dengue virus - Zhifeng Li; Xian Qi; Minghao Zhou; Changjun Bao; Jianli Hu; Bin Wu; Shenjiao Wang; Zhongmin Tan; Jianguang Fu; Jun Shan; Yefei Zhu; Fenyang Tang (Archives of Virology, 2013)

Molecular genetic studies of gene identification for sarcopenia - Li-Jun Tan; Shan-Lin Liu; Shu-Feng Lei; Christopher J. Papasian; Hong-Wen Deng (Human Genetics, 2012)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

High-mobility group box 1 exacerbates concanavalin A-induced hepatic injury in mice - Quan Gong; Hui Zhang; Jun-hua Li; Li-hua Duan; Shan Zhong; Xiao-ling Kong; Fang Zheng; Zheng Tan; Ping Xiong; Gang Chen; Min Fang; Fei-li Gong (Journal of Molecular Medicine, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells - Chen-Jing Wang; Chang-Ping Hu; Kang-Ping Xu; Qiong Yuan; Fu-Shuang Li; Hui Zou; Gui-Shan Tan; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Two new N -oxide Lycopodium alkaloids from Huperzia serrata - Heng-Bin Wang; Chang-Heng Tan; Jun-Jie Tan; Shi-Jin Qu; Yi-Lei Chen; Yi-Ming Li; Shan-Hao Jiang; Da-Yuan Zhu (Natural Product Research, 2009)

An efficient method to enhance gene silencing by using precursor microRNA designed small hairpin RNAs - Zhixin Shan; Qiuxiong Lin; Chunyu Deng; Xiaohong Li; Wei Huang; Honghong Tan; Yongheng Fu; Min Yang; Xi-Yong Yu (Molecular Biology Reports, 2009)

Protective effects of daviditin A against endothelial damage induced by lysophosphatidylcholine - De-Jian Jiang; Jun-Lin Jiang; Gui-Shan Tan; Yan-Hua Du; Kang-Ping Xu; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)